Enhanced photoelectrochemical performance of ZnO nanorod arrays decorated with CdS shell and Ag2S quantum dots. (March 2017) - Holi, Araa Mebdir; Zainal, Zulkarnain; Talib, Zainal Abidin; Lim, Hong-Ngee; Yap, Chi-Chin; Chang, Sook-Keng; Ayal, Asmaa Kadim
Abstract: Ternary nanostructured Ag2 S/CdS/ZnO thin film was prepared by using a simple low-cost hydrothermal method. The hexagonal phase of ZnO nanorods and CdS shells combined with monoclinic Ag2 S quantum dots resulted in improved optical and photoelectrochemical properties. CdS shell with high absorption property efficiently compliment the energy levels of ZnO and improved the ability of light absorption. Furthermore, narrow band gap Ag2 S also played a vital part in the light harvesting. The photoelectrochemical performance of the ternary nanostructured Ag2 S/CdS/ZnO NRs was investigated in a mixture of Na2 S and Na2 SO3 aqueous solutions under visible light illumination. The Ag2 S/CdS/ZnO NRs were found to be more efficient than ZnO NRs, CdS/ZnO NRs, and Ag2 S/ZnO NRs as this particular sample gave a maximum photocurrent of 5.69 mA cm −2, which is around 2 and 1.5 times greater than CdS/ZnO NRs and Ag2 S/ZnO NRs, respectively. Besides that, it was found that this ternary film possessed 15 times higher photocurrent density than plain ZnO NRs. This is attributed to the larger amount of visible light absorbed by the ternary nanostructured composite. Highlights: A new photoelectrode has been fabricated using hydrothermal method. Ternary structure shows better photocurrent density. Ternary structure shows substantial improvement in charge collection efficiency. Co-sensitized exhibits strong light absorption in visible region.